ChemInform Abstract: Lanthanide‐Catalyzed Reversible Alkynyl Exchange by Carbon—Carbon Single‐Bond Cleavage Assisted by a Secondary Amino Group. Issue 52 (6th December 2016) - Shao, Yinlin; Zhang, Fangjun; Zhang, Jie; Zhou, Xigeng
Abstract: Lanthanide‐catalyzed alkynyl exchange through C—C single‐bond cleavage assisted by a secondary amino group is reported.